The Market Efficiency of the Stock Market in India - Rahman, Sahnawaz (2011)
The greatest and engendering event in the Twenty first century is capital and financial market revolution and reformation especially for India. Efficient Market Hypothesis has attracted numbers of studies in empirical finance particularly in determining the market efficiency of an emerging financial market which produced conflicting and inconclusive outcomes. This paper tests the efficiency of the Indian Capital Market in its semi-strong form and weak form of Efficient Market Hypothesis (EMH). For the purpose, 30 Group ‘A’ stocks of two major stock indices viz. National Stock Exchange (NSE) and Bombay Stock Exchange (BSE) that represent the Indian Capital Market have been taken. Monthly averages of NSE & BSE have taken in order to test the efficiency of Indian Capital Market. Karl-Pearsons Correlation , Runs Test, Spearman’s Rank Correlation and regression equations have been used to analyze and determine the degree and direction of the relationship between the variables involved. The results suggest having significant impact on Indian Capital Market, which leads to the conclusion that Indian Capital Market is semi-strong form and weak form efficient.